2009
DOI: 10.1021/ci900163t
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Conformational Biasing: A New Method for Focusing Conformational Ensembles on Bioactive-Like Conformers

Abstract: Computational approaches that rely on ligand-based information for lead discovery and optimization are often required to spend considerable resources analyzing compounds with large conformational ensembles. In order to reduce such efforts, we have developed a new filtration tool which reduces the total number of ligand conformations while retaining in the final set a reasonable number of conformations that are similar (rmsd < or = 1 A) to those observed in ligand-protein cocrystals (bioactive-like conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…8 Much work has been previously published proposing different structural criteria for focusing conformational ensembles on bioactive conformations. 9 A pioneering work by Diller and Merz suggested that bound conformations tend to have larger polar and apolar solvent accessible surface areas (SASA), fewer internal interactions, and a larger Radius of Gyration (ROG) than random conformations. 10 This was explained by the hypothesized tendency of small molecules to unfold when binding to a protein in order to maximize favorable interactions with key functionalities within the protein binding site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Much work has been previously published proposing different structural criteria for focusing conformational ensembles on bioactive conformations. 9 A pioneering work by Diller and Merz suggested that bound conformations tend to have larger polar and apolar solvent accessible surface areas (SASA), fewer internal interactions, and a larger Radius of Gyration (ROG) than random conformations. 10 This was explained by the hypothesized tendency of small molecules to unfold when binding to a protein in order to maximize favorable interactions with key functionalities within the protein binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been previously published proposing different structural criteria for focusing conformational ensembles on bioactive conformations . A pioneering work by Diller and Merz suggested that bound conformations tend to have larger polar and apolar solvent accessible surface areas (SASA), fewer internal interactions, and a larger Radius of Gyration (ROG) than random conformations .…”
Section: Introductionmentioning
confidence: 99%
“…So, the methods for conformational analysis and sampling of small organic molecules remain a very active field of research. 10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] New developments have taken advantage of increased computational resources as well methodological advances, e.g. around the distance geometry approach.…”
Section: Introductionmentioning
confidence: 99%
“…via pharmacophore-based or scaffold-hopping searches, and can also be used in conjunction with docking. So, the methods for conformational analysis and sampling of small organic molecules remain a very active field of research. , New developments have taken advantage of increased computational resources as well methodological advances, e.g. around the distance geometry approach. , Overall, these efforts have led to the availability of high-throughput conformation generators, such as CAESAR, Catalyst, ConfGen, MOE Conformation Import, Omega, and Rubicon .…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] A number of lead design strategies spanning frontier areas of drug design like QSAR, 27,28 high-throughput screening, 29 pharmacophore mapping, 30 combinatorial libraries, 31 traditional drug design techniques, 32,33 etc., have been used either individually or as a combination to understand the nuances underlying specificity and selectivity in kinases, which are one of the most sought after class of druggable targets. Different aspects of kinases like size of gatekeeper residue, 34 metabolic properties of the target involved in signal transduction, 35,36 protonation switch in drug binding, 37 network analysis and fingerprint of structure and sequence of kinome, 38 recognition properties affecting selectivity, 39 chemogenomics, 40 and fragment-based drug design [41][42][43][44] have been probed. In spite of the ongoing efforts, kinase inhibitors lack specificity and selectivity.…”
Section: Introductionmentioning
confidence: 99%